OPTIMALISASI INLISLite DALAM TEMU KEMBALI INFORMASI DI DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA PAYAKUMBUH - Liana Utami; Sri Wahyuni (Publication Library and Information Science, 2023)
The main problem in this thesis is the existence of obstacles encountered in information retrieval by users using the INLISLite software at the Payakumbuh City Library and Archives Service. The purpose of this study was to find out how to optimize information retrieval facilities in the information retrieval process by users at the Payakumbuh City Library and Archives Service. This type of research is a mixed methods method with a descriptive approach and a type of field research. Data collection techniques through observation, interviews and documentation. Data analysis techniques start from data reduction, data presentation and drawing conclusions. Guarantee the validity of the data in this study using source triangulation and technique triangulation. The results of the study show that (1) the performance and system coverage of the INLISLite software in the information retrieval process are good. The ability of the INLISLite software to find only the information needed is good, this result can be seen from the search results using the recall formula and the search results table which shows that the relevance of the documents found is 100% and fully relevant. The time needed by the INLISLite software to find the required information is fast. The average search time is 3.83 seconds. (2) Constraints in optimizing INLISLite software in information retrieval at Archives, namely the INLISLite software, especially the OPAC feature which can only be accessed using a special computer that has been provided and can also use a mobile phone but must log into the Payakumbuh City Library and Archive Service wifi.